The Smart Spin Wheel Educational Game Tool (ROPTAR) is an Alternative Screening Media Child Development - Rita Yulifah; Tri Johan Agus Yuswanto (Aloha International Journal of Health Advancement (AIJHA), 2025)
Children are human resource assets. To become a quality asset, it needs to be prepared from an early age for both growth and development. Stimulation, Detection, Early Growth and Development Intervention (SDIDTK) is one of the efforts to improve the quality of children by monitoring to optimize children's development regularly and periodically from an early age. Development monitoring is carried out using the standard Pre-Screening Development Questionnaire (KPSP). The use of KPSP during and as a result of the development of KPSP in the form of an Android application is one-way, so that children, parents and the user community are passive. This research is development research (research and development) which aims to develop a standardized child development assessment instrument, namely KPSP and determine the feasibility of development results. This research uses a prototype development model. Data collection used a questionnaire sheet, expert testing was carried out by two people, namely a growth and development specialist and a media expert, data analysis was descriptive. The development of a standardized instrument is based on the form, number of questions and algorithm. The results of development research are educational game products whose suitability has been tested by experts and by product users. Evaluation of development trial results: 1) the form of the 8 components has an overall average of 91% in the good category, 2) the content of the addition of 9-10 questions to 12 questions, 3) the algorithm of the 6 evaluation components with a minimum score of 87 and a maximum score of 92 is considered positive. The average development quality results according to users in terms of functionality, efficiency and usability were 93.33% in the good category. The effectiveness test results obtained were p=0.001 (p < 0.005). So it can be concluded that the development of the Pre-Developmental Screening Questionnaire (KPSP) in the form of an educational game tool is suitable for use as a tool to help monitor children's growth and development. Keywords: development; pre-screening questionnaire; smart spin wheel educational game tool (ROPTAR)